The role of lipids and lipids lowering drugs in human papillomavirus (HPV) and HPV-associated cancers - Ehsan Shabani; Aida Hasanzadi; Omer Qutaiba B. Allela; Radhwan Abdul Kareem; Riyad E. Abed; Ali M. Ali Al-Nuaimi; Zainab H. Athab; Shiva Khodarahmi (Infectious Agents and Cancer)
Abstract Both women and men are now confronted with the grave threat of cancers caused by the human papillomavirus (HPV). It is estimated that 80% of women may encounter HPV over their lives. In the preponderance of cases involving anal, head and neck, oral, oropharyngeal, penile, vaginal, vulvar, and cervical malignancies, high-risk HPV (HR-HPV) is the causative agent. In 2019, HPV is believed to have been the cause of 620,000 new cases of cancer in women and 70,000 new cases of cancer in men worldwide. The bulk of the 530,000 cervical cancer cases (~ 270,000 fatalities) caused by HPV infection (86% of cases, 88% of deaths) happen in poor nations each year. Lipid metabolism is crucial in HPV infection and cancer development related to HPV. One of the most noticeable metabolic abnormalities in cancer is lipid metabolism reprogramming, in which cancer cells dysregulate lipid metabolism to obtain sufficient energy, building blocks for cell membranes, and signaling molecules necessary for invasion, metastasis, proliferation, and survival. Moreover, HPV proteins' stimulation of lipid production in infected cells will probably have a significant effect on oncogenesis. In addition, lipids are critical in producing cellular energy, the epithelial-mesenchymal transition (EMT) process, and therapy resistance of HPV-related cancers (HRCs). Therefore, lipids are essential in HPV infection and HRC development and may also be an important target for new approaches associated with treatments during HPV infection or cancer development. This review study looked at the role of lipids and lipid-lowering drugs in HPV and related cancers. Graphical Abstract